﻿Remote ischemic preconditioning combined with atorvastatin improves memory after global cerebral ischemia-reperfusion in male rats - Azim Hedayatpour; Maryam Shiasi; Peyman Modarresi; Alieh Bashghareh (Belgorod National Research University, 2022)
Introduction: Damage to hippocampus can occur through ischemia. Memory problems are among the most significant disabilities after stroke. Therefore, improving memory is of great interest in helping post-stroke patients. This study demonstrated that intraperitoneally injection of ﻿atorvastatin﻿ with a short cycle of ischemia-reperfusion in the left femoral artery improved hippocampal CA1 neurons injury and memory problems after global cerebral ischemia. Materials and methods: In this article survey, we used 64 animals. Rats were divided into 8 groups, (n=8). Group 1: control; group 2: sham; group 3: global cerebral ischemia (GCI) only; group 4: remote ischemic preconditioning (RIP) + GCI; group 5: GCI + ﻿atorvastatin﻿ (﻿ATO﻿); group 6: GCI + vehicle; group 7: RIP + GCI + ﻿ATO﻿; group 8: RIP + GCI + vehicle. We created global cerebral ischemia (GCI) with 20 min occlusion of the Common carotid artery. Results and discussion: Remote ischemic preconditioning could improve rats performance in water maze tests along with a decrease in neuronal death. Also, ﻿atorvastatin﻿ combined with remote ischemic preconditioning was more effective for memory improvement and reduction of neuronal death. Inconsistent with our result, the function of the animals in the ischemia group was impaired. CA1 hippocampal neurons have an important role in memory and learning, and they can be damaged after cerebral ischemia. Therefore, ischemia can create memory problems. Remote ischemic preconditioning and ﻿atorvastatin﻿ had a neuroprotective effect and could improve rat performance in water maze test. Conclusion: This study showed that remote ischemic preconditioning with ﻿atorvastatin﻿ could improve CA1 neuronal injury and memory. Graphical abstract: